Pengaruh Beban Kerja, Pengalaman, dan Skeptisme Profesional Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan (Studi Empiris pada BPK RI Perwakilan Propinsi Sumatera Barat) - Yulia Eka Sari; Nayang Helmayunita (Wahana Riset Akuntansi, 2018)
This research aims to find new evidence about the factors that effect the workload,experience and professional skepticism to fraud detection ability of auditor. Respondents in this research is the auditor’s who work at Badan Pemeriksa Keuangan (BPK) Padang Province Representation. Collecting data of thid study using a questionnaires submitted to 42 auditors. From questionnaires distributed 36 questionnaires (85,71%) were completed and can be processed. The data of this study using primary data directly through a questionnaires and analyzed using SPSS version 22 for windows. The data were analyzed to test the hypothesis using multiple linear regression analysis approach Then, the research using multiple regression method found that only workload having a negative on the fraud detection ability of auditor. While, experience, and professional skepticism having a positive effect on the fraud detection ability of auditor.Keywords: workload, experience, professional skepticism, and fraud detection ability of auditors